Smoking status in relation to serum folate and dietary vitamin intake - Vardavas, Constantine I (BioMed Central, 2008)
OBJECTIVE: Cigarette smoke itself is an abundant source of free radicals and a major cause of oxidative stress, to which plasma antioxidants function as a vital protective and counterbalancing mechanism. The objective of this study was to investigate into the relationship between smoking status and serum and dietary micronutrient concentrations. DESIGN: Cross-sectional study SUBJECTS – SETTING: 502 farmers from the Valley of Messara in Crete were randomly selected and examined. Complete three-day and 24-hr recall questionnaires were collected along with anthropometrical, physical activity and clinical data from all participating subjects. RESULTS: After adjusting for age, gender and number of fasting days adhered to per year, current smokers were found to have a lower dietary intake of vitamin C (112.1 mg vs. 136.4 mg, p = 0.03), fibre (16.6 g vs. 19.1 g, p = 0.006) and fruits and vegetables (339 g vs. 412 g, p = 0.014), while dietary vitamin B(1 )intake was found to be higher (1.7 mg vs. 1.4 mg, p = 0.02) in comparison to non/ex smokers. Dietary intake of meat, folate and vitami A, E, B(2), B(6 )and B(12 )did not differ between the groups. Controlling age, gender, fasting days and dietary micronutrient intake, serum folate levels were found to be lower among smokers (geometric mean 15.3 nmol/L vs. 17.7 nmol/L, p = 0.023), while serum iron and vitamin B(12 )levels were not affected by smoking status. CONCLUSION: Current smoking status affects dietary nutrient intake as well as plasma folate levels. The above coherence between antioxidant depletion and reduced antioxidant intake may predispose smokers to the premature development of tobacco related mortality and morbidity.